Mafhum Maharah Qiraah dan Maharah Kitabah - Hardiyanti, Putri (Islamic Education, 2022)
In Arabic there are four basic language skills, namely listening skills (Maharah Istima'), speaking skills (Maharah Kalam), reading skills (Maharah Qiraah), and writing skills (Maharah Kitabah). Listening and speaking are two skills related to the use of Arabic in the spoken realm while reading and writing are two skills related to the use of Arabic in the written realm. These four aspects are important aspects in learning Arabic, because these four skills cannot be separated. Because the position of these four skills is very supportive in the achievement of language skills. Writing this article aims to describe the concept of Fahmul Mahaarah al-Lughowiyah, namely about Maharah Qiraah and Maharah Kitabah. Which includes the understanding, classification, teaching principles, and teaching techniques of Maharah Qiraah and Kitabah.